Gardeners of the forest: Effects of seed handling and ingestion by orangutans on germination success of peat forest plants - Tarszisz, E.; Tomlinson, Sean; Harrison, M.; Morrough-Bernard, H.; Munn, A. (Wiley-Blackwell, 2018)
© 2017 The Linnean Society of London, Biological Journal of the Linnean Society. The passage of seeds through an animal's gut can improve the probability of germination for some plants. We followed 13 Bornean orangutans (Pongo pygmaeus wurmbii) in a peatland forest in the Sabangau Forest, Central Kalimantan and collected their faecal samples opportunistically. From these samples, we identified 13 angiosperm species' seed, which ranged from small (0.61 ± 0.10 cm) to moderately large (2.16 ± 0.24 cm) seeds. We compared the germinability of the seeds of five species that were defecated by orangutans with conspecific seeds that were manually extracted from fruits and those from whole (intact) fruits, with the aim to test for effects of gut passage on germination. Overall germination success increased and the time taken to obtain 50% germination reduced as a result of interactions with orangutans in all species except Elaeocarpus mastersii. There was no germination success for three species (Nephelium maingayi, Diospyros areolata and Sandoricum beccarianum) from unhandled fruits during the 60-day trial period, and the remaining two species both had less than 100% germination. For all species, except Campnosperma coriaceum, the total germination fraction was substantially higher for manually extracted seeds than for defecated seeds. From these experiments, we concluded that while orangutans may not enhance germinability via ingestion and defecation, these large-bodied frugivores are functional dispersers for many plant species via their long-distance movements. Furthermore, the increased germinability of manually extracted seeds suggests that spitting of seeds by foraging orangutans could be of unrecognized importance in the demography of peat forest plants.